(untitled) - Drake, Ellen (Philadelphia.PA, 2006)
The Saunders Pharmaceutical Word Book contains the correct spelling and capitalization of over 27,000 brand-name and generic drugs with dosage forms, investigational drug names and codes, chemotherapy protocols, trademarked dosage forms, and drug categories/classes. Although it is not a prescribing reference, it also contains the indications of approved drugs and standard dosages.
Keywords: Drugs,Pharmaceutical Preparations,Thuốc,Chế phẩm dược